231k views
5 votes
Simplify a^2-3a/a^3-8a^2+12a to lowest terms

1 Answer

4 votes

In order to simplify a fraction, we have to find a common factor in both numerator and denominator. So, let's start by factor the expressions completely: at the numerator we have


a^2-3a = a(a-3)

At the denominator we have


a^3-8a^2+12a = a(a^2-8a+12) = a(a-2)(a-6)

So, the fraction can be written as


(a(a-3))/(a(a-2)(a-6))

You can see that there is a factor
a in common, that can be simplified:


(a(a-3))/(a(a-2)(a-6)) = (a-3)/((a-2)(a-6))

User Shandra
by
5.8k points